Effect of having theoretical question in final examination for ‘introduction to microelectronics’ (ELE 245) / Shaiful Bakhtiar Hashim, Norhidayatul Hikmee Mahzan and Nur Syahirah Kamarozaman - Hashim, Shaiful Bakhtiar; Mahzan, Norhidayatul Hikmee; Kamarozaman, Nur Syahirah (2019)
Introduction to Microelectronics (ELE 245) is one of the compulsory courses for Electrical Engineering student majoring in electronics. This course basically exposing students on basic concept of physics and properties of semiconductor, PN junction, fabrication process and integrated circuits (IC) design flow and layout. In general, there are several factors that influenced students’ in academic performance, such as students’ engagement in class, attitude, effects of social support and lecturer’s teaching method. This paper studied the effect of having theoretical question in final examination for ELE 245 course. In this paper, the respondent is comprised of students’ whom taking this course throughout previous 3 semesters. The data(s) were collected from Result Entry System, which then use to calculate the overall marks, including test, assignment, quiz, laboratory report and final examination thus producing the final grade for each student. From the results, it was found that the theoretical type of question was not favourable to be answered compared to calculations or design questions. In order to improve students’ understanding in theoretical part we proposed to develop an experimental learning process environment.